A 2.4-GHz RF CMOS transceiver for wireless sensor applications - Carmo, J. P. (2005)
A radio-frequency transceiver chip was designed in a UMC RF 0.18 µm CMOS process. The target RF frequency is 2.4 GHz ISM band. The specifications are a sensibility of -60 dBm and a power transmission of 0 dBm. The power supply of the transceiver is 1.8 V. Simulations show a power consumption of 10.7 mW. Innovative topics concerning efficient power management was taken into account during the design of the transceiver.